Long-standing Persistent Atrial Fibrillation Ablation: the Role of the Inter- and Intra-atrial Bundles - Mitchell, Russell; Bonilla Isaza, Cesar Augusto (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Catheter ablation has become the mainstream treatment of atrial fibrillation, but still remains a challenge in those patient with persistent and long standing persistent atrial fibrillation. In addition of isolation of the pulmonary veins, any other areas that can trigger or perpetuate atrial fibrillation need to be isolated. Current technologies may allow to effectively deliver permanently lasting lesions, and therefore improve clinical outcomes after ablation. The specialized conduction system including the Bachmann and septopulmonary bundles, are important substrate targets for the management of atrial fibrillation. The anatomical location of these fibers, and the corresponding approach for ablation are described in this case.